Business plan - JobMatch Sdn Bhd - Mohd Afandi, Nurdiana (2019)
JobMatch Sdn Bhd (JobMatch) is a startup company founded in 2018. JobMatch is a private limited company equally owned by Diana Afandi and Gan Soo Hong. As the name implies, JobMatch offers a job-matching platform that provide a holistic solution to cater for individuals that is looking for a job (“Job Seekers”) and the organizations or companies that is looking for the right talent (“The Companies/Employers/Hiring Managers”) by offering a service platform that provides a mobile/desktop job discovery and matching application that allows users to browse for jobs and connect with the employers anytime and anywhere locally.